Association between occupational stress and mental health of nurses during the COVID‐19 pandemic: A cross‐sectional research - Huiying Wu; Kewen Qi; Bonan Luan; Zhengwen Liu; Qingyun Zhao (Wiley, 2023)
Abstract Aim This study is aimed to explore the association between the occupational stress and mental health among Chinese nurses during the COVID‐19 pandemic. Design Cross‐sectional study. Methods There were 2913 nurse participants enrolled in the study. Demographic characteristics and other data were measured by a self‐reported questionnaire. Occupational stress was measured by using the effort-reward imbalance (ERI) questionnaire. Mental health was measured by the Patient Health Questionnaire‐9 and the General Anxiety Disorder‐7. Results Among the participants, 14.32% (417) experienced ERI; 8.1% (237) and 7.2% (210) reported depressive and anxiety symptoms, respectively. Compared with a reference group at the lowest quartile of the ERI, participants in the highest quartile had an adjusted odds ratio (OR) (95% CI) of 11.17 (4.42, 28.25) for incident depressive symptoms. For anxiety symptoms, the OR and 95% CI was 2.28 (1.21, 4.29). The ERI was shown to have a detrimental effect on mental health, especially depressive symptoms.